Gravity with Intermediate Goods Trade - Sujin Sujin; E. Young Song (East Asian Economic Review (EAER), 2017)
This paper derives the gravity equation with intermediate goods trade. We extend a standard monopolistic competition model to incorporate intermediate goods trade, and show that the gravity equation with intermediates trade is identical to the one without it except in that gross output should be used as the output measure instead of value added. We also show that the output elasticity of trade is significantly underestimated when value added is used as the output measure. This implies that with the conventional gravity equation, the contribution of output growth can be substantially underestimated and the role of trade costs reduction can be exaggerated in explaining trade expansion, as we demonstrate for the case of Korea's trade growth between 1995 and 2007.
Keywords: F12; F14; F15; 330; Gravity Equation; Gross Output; Intermediate Goods Trade; Global Value Chains; Fragmentation